Modern Dutch grammar a practical guide - Oosterhoff, Jenneke A. (London Routledge, 2015)
"Modern Dutch Grammar: A Practical Guide is an innovative reference guide to Dutch, combining traditional and function-based grammar in a single volume. With a strong emphasis on contemporary usage, all grammar points and functions are richly illustrated with examples. The Grammar is divided into two parts. Part A covers traditional grammatical categories such as nouns and verbs. Part B is carefully organized around language functions and contexts such as:Giving and seeking informationDescribing processes and resultsExpressing attitudes, mental states and emotionsRegisters and styleFormal and informal communication, e.g. youth talk Main features of the Grammar include:Clear, succinct and jargon-free explanationsExtensive cross-referencing between the different sectionsEmphasis on areas of particular difficulty for learners of DutchThis is the ideal reference grammar for learners of Dutch at all levels, from elementary to advanced; no prior knowledge of grammatical terminology is assumed and an index of grammatical terms is provided. This Grammar is complemented by a companion website featuring related exercises and activities to reinforce learning."--Provided by publisher.
Includes indexes.
Keywords: Dutch language -- Textbooks for foreign speakers -- English; Dutch language -- Grammar -- Problems, exercises, etc